LEGAL DRAFTING UNTUK PERUBAHAN HUKUM: TANTANGAN DAN SOLUSI DALAM PENYUSUNAN REGULASI DAN UNDANG- UNDANG YANG ADAPTIF - Akhmad Zaki Yamani (JOURNAL OF LAW AND NATION, 2024)
This study examines two key case studies in legal regulation to illustrate successes and failures in legal drafting: the implementation of the General Data Protection Regulation (GDPR) in the European Union and the proposed Stop Online Piracy Act (SOPA) in the United States. GDPR is praised as a successful example of regulation that has adapted to technological changes and privacy needs, thanks to its flexible and responsive design. In contrast, SOPA failed due to its perceived overreach, which could potentially threaten freedom of speech and innovation on the internet. The failure of SOPA highlights the importance of considering the broad implications of technology and social norms, as well as the need for active involvement from various stakeholders in the lawmaking process. Findings from both cases underscore the need for flexibility and participation in legal drafting to create effective and relevant regulations. This research provides insights into how a multidisciplinary approach and stakeholder engagement can enhance regulatory effectiveness in addressing modern challenges.